Pengembangan Media Pembelajaran “SKIAN” (Sejarah Kebudayaan Islam Animasi) Berbasis Aplikasi iSpring Suite pada Mata Pelajaran Sejarah Kebudayaan Islam Kelas X di SMA Madinatul Ulum - Fitri Khoirotun Nasyiroh; Hidayatur Rohmah (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the development of interactive learning media for Sejarah Kebudayaan Islam (Islamic Cultural History, SKI), amidst the continued dominance of conventional methods that tend to be less engaging and the underutilization of Information and Communication Technology (ICT), which negatively affects students' learning interest and comprehension. The aim of this research is to develop an interactive learning media titled